Carotid intima-media thickness in arterial hypertension patients with and without metabolic syndrome - G. Kh. Sharipova; T. V. Balakhonova; V. B. Mychka; I. E. Chazova (Кардиоваскулярная терапия и профилактика, 2009)
The review presents the studies on common carotid artery intima-media thickness in arterial hypertension patients with and without metabolic syndrome (MS). The authors discuss pathogenetic aspects and the risk factor effects on intima-media thickness in patients with and without MS.